Price and Product Quality as Determinants of Consumer Purchase Decisions for Spare Parts at CV Fajar Motor - August Halomoan Siregar; Denni Denni; Veronica Veronica (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2025)
This study aims to analyze the influence of price and product quality on purchasing decisions for spare parts at CV Fajar Motor. In today’s increasingly competitive automotive market, understanding the key factors that drive consumer purchase behavior is critical for business success. Employing a quantitative survey method, questionnaires were distributed to customers of CV Fajar Motor. The collected data were analyzed using multiple linear regression to examine both the partial and simultaneous effects of price and product quality on purchasing decisions. The results reveal that both price and product quality significantly and positively impact consumers' purchasing decisions, whether considered individually or together. These insights provide valuable strategic guidance for CV Fajar Motor to optimize pricing strategies and enhance product quality, ultimately improving customer satisfaction and loyalty.